HUKUM ISLAM DAN REALITAS MASYARAKAT (Upaya Memitrakan Konsep Hukum dengan Realitas Sosial) - Firdaus achmad (The Pontianak State Institute of Islamic Studies, 2013)
Life is a relationship between the activities of the occupant totality of the universe. For the sake of keeping the arranged activity, social and human as rational beings, designing various rules which then crystallization into a hunk of law. Awareness of the existence of human omnipotence of God in the governance of the universe of the universe, inspire omniscience of God involvement in the process of building the legal arrangement. Religious rules contained in the scriptures, as a description of his omnipotence and omniscience of God, an option spiritualistic when humans are exposed to must resolve the problems of life that is realistic. The existence of empty space between the realistic problems in your life with religious rules in the scriptures, human require to maximize the potential of rationality which naturally are able to present a realistic and the positive facts. Using the second option, the rule of God and product capabilities most rational way out is ideal. However, sometimes problems in your life require realistic humans tend to choose one of the two choices it. This condition necessitates the existence of thought on human wisdom to face realistic problems in your life.